FRI0582 Could MRI of the Hand Improve the Accuracy of the 2010 ACR/EULAR Criteria for Rheumatoid Arthritis?. (9th June 2015) - Marques, D.; Lisbona, M.P.; Orpinell, L.; Solano, A.; Ares, J.; Almirall, M.; Salman-Monte, T.; Maymo, J.
Abstract : Objectives: To analyze whether the addition of inflammatory findings or erosions on hand MRI improve the accuracy of ACR/ EULAR 2010 RA classification criteria in early arthritis. Methods: Cross-sectional study of patients with early arthritis (defined as the presence of at least one inflamed joint, less than a year since the start of the first symptoms and without meeting the ACR/EULAR 2010 criteria) referred to the Early Arthritis Clinic at Hospital Mar (PSMAR, Barcelona). At baseline, demographic (age, gender), disease-related (median of disease duration in months, serum levels of RF U/ml and ACPA U/ml, presence of radiological erosions on hands and feet) and previous treatments (NSAIDs, glucocorticoids (GCs) and synthetic DMARDs) were recorded. Clinical data, laboratory tests and functional disability were collected. MRI of the dominant hand (h-MRI) was performed and score according to the OMERACT RAMRIS recommendations (RAMRIS-synovitis (0-21), RAMRIS-bone edema (0-69) RAMRIS-erosions (0-230)), tenosynovitis (0-26) and total inflammation (sinovitis plus bone edema plus tenosynovitis, 0-116) in wrist and 2nd to 5th MCP joints were recorded. We used the presence of any lesion on h-MRI added 2010 RA criteria to improve the diagnostic accuracy of these criteria. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of the ACR/EULAR 2010 criteria alone and associated with h-MRI parameters were analyzed using fulfillment of the ACR 1987 criteria at one year follow-up as standard reference. All data was analyzed using the SPSS v.18. Results: Sixty-one patients with early arthritis out of 199 (30.6%) who did not fulfilled the ACR/EULAR 2010 criteria for the diagnosis of RA at baseline and with avalaible data of h-MRI were included. Demographic, clinical and h-MRI data at baseline will be shown in an additional Table . The mean (±SD) RAMRIS score for synovitis was 4.86 (±2.61), for RAMRIS bone-edema was 6.81 (±3.61), for RAMRIS-erosions was 4.42 (±4.84), for tenosynovitis was 4.63 (±5.3), total inflammation was 10.6 (±13.11) and Total RAMRIS of 12.98±11.25). The table showed the sensitivity, specificity, PPV, NPV and diagnostic accuracy of the ACR/EULAR 2010 criteria alone or associated with MRI parameters using as reference standard fulfil the 1987 RA criteria at one year. Conclusions: Our results suggest that including baseline inflammatory findings and erosions from h-MRI in the ACR/EULAR 2010 criteria using the 1987 ACR criteria as a reference at one year, does not improve the diagnostic accuracy in our patients with early arthritis. References: Tamai M et al. Ann Rheum Dis 2014;73:2219-20. Nieuwenhuis WP et al. Ann Rheum Dis 2014;0:1-2. Disclosure of Interest: None declared